2016
DOI: 10.1016/j.bbamem.2016.05.022
|View full text |Cite
|
Sign up to set email alerts
|

Single-step electrical field strength screening to determine electroporation induced transmembrane transport parameters

Abstract: The design of effective electroporation protocols for molecular delivery applications requires the determination of transport parameters including diffusion coefficient, membrane resealing, and critical electric field strength for electroporation. The use of existing technologies to determine these parameters is time-consuming and labor-intensive, and often results in large inconsistencies in parameter estimation due to variations in the protocols and setups. In this work, we suggest using a set of concentric … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 57 publications
(78 reference statements)
0
6
0
Order By: Relevance
“…The non-homogeneous sample conductivity could be addressed by applying, high-frequency bipolar pulse protocols (H-FIRE) which mitigate the impedance differences ( Bhonsle et al, 2015 ; Sano et al, 2015 ) but unfortunately require delivery of higher energy than longer unipolar irreversible electroporation (IRE) pulses ( Murovec et al, 2016 ; Sweeney et al, 2016 ). However, universal protocols, which allow countering or optimising all the limitations described above, are still not available ( Pakhomova et al, 2011 ; Blumrosen et al, 2016 ; Yildirim et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…The non-homogeneous sample conductivity could be addressed by applying, high-frequency bipolar pulse protocols (H-FIRE) which mitigate the impedance differences ( Bhonsle et al, 2015 ; Sano et al, 2015 ) but unfortunately require delivery of higher energy than longer unipolar irreversible electroporation (IRE) pulses ( Murovec et al, 2016 ; Sweeney et al, 2016 ). However, universal protocols, which allow countering or optimising all the limitations described above, are still not available ( Pakhomova et al, 2011 ; Blumrosen et al, 2016 ; Yildirim et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…We model the probability of cell death after treatment as p D , which can be estimated as a function of the experimental conditions. The cell death rate associated with a particular experimental setup can be measured based on the fluorescent intensity of the cells present in the training data, as this variable attests to the cells' condition (43,44). Specifically, a signal indicating high fluorescent intensity can be taken to indicate reduced cell viability, since it means that membrane permeability is greater and consequently the cell has a higher probability of dying.…”
Section: Single Treatment Effect Analysismentioning
confidence: 99%
“…We also showed ex vivo that electroporation-based molecular harvesting extracts proteome with tissue-specific signatures for liver [ 23 ]. In the previous work in vitro , we showed that electroporation enables molecular transport out of the cells up to 3.9mm around the electrode [ 34 ]. Here we demonstrate the ability to gather the ex vivo extracted molecules for the diagnostics.…”
Section: Introductionmentioning
confidence: 99%